2008
DOI: 10.1124/mol.108.050732
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Human Pregnane X Receptor Activation by the Hops Constituent Colupulone

Abstract: Hops extracts are used to alleviate menopausal symptoms and as an alternative to hormone replacement therapy, but they can produce potentially harmful drug-drug interactions. The nuclear xenobiotic receptor pregnane X receptor (PXR) is promiscuously activated by a range of structurally distinct chemicals. It has a key role in the transcriptional regulation of genes that encode xenobiotic metabolism enzymes. In this study, hops extracts are shown to induce the expression of numerous drug metabolism and excretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 59 publications
2
53
0
Order By: Relevance
“…It has been shown that an ethanolic extract of hops of unknown chemical composition increases PXR-mediated transcriptional activity (46), as assessed in an in vitro cellbased luciferase reporter gene assay (Table I). Comparative analysis indicates that the extent of PXR activation by the ethanolic extract of hops is similar to that obtained with St. John's wort and Gugulipid®.…”
Section: Humulus Lupulus (Hop Extract)mentioning
confidence: 99%
“…It has been shown that an ethanolic extract of hops of unknown chemical composition increases PXR-mediated transcriptional activity (46), as assessed in an in vitro cellbased luciferase reporter gene assay (Table I). Comparative analysis indicates that the extent of PXR activation by the ethanolic extract of hops is similar to that obtained with St. John's wort and Gugulipid®.…”
Section: Humulus Lupulus (Hop Extract)mentioning
confidence: 99%
“…Structure-based methods such as docking enable one to determine whether molecules will fit and have favorable interactions in crystal structures and homology models. Both of these approaches have been widely used for identifying PXR agonists and antagonists (Ekins et al, 2007(Ekins et al, , 2008aYasuda et al, 2008;Biswas et al, 2009;Kortagere et al, 2009Kortagere et al, , 2012Li et al, 2013) for which crystal structures exist (Watkins et al, 2001(Watkins et al, , 2002(Watkins et al, , 2003aChrencik et al, 2005;Noble et al, 2006;Xue et al, 2007a,b;Teotico et al, 2008). The Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This could also explain why Hyp3 was frequently retrieved by both pharmacophores and docking. It is widely known from our previous work and the many crystal structures (Watkins et al, 2001(Watkins et al, , 2002(Watkins et al, , 2003aChrencik et al, 2005;Noble et al, 2006;Xue et al, 2007a,b;Teotico et al, 2008) that hydrophobicity is important for interaction in the LBD and at the SRC-1 antagonist site (Ekins et al, 2007). The majority of the phloroglucinol derivatives were found to have docking scores lower than the comparator compounds hyperforin and ketoconazole, suggesting that they were unlikely to behave as agonists or antagonists, respectively.…”
Section: Interaction Of Phloroglucinols With Hpxrmentioning
confidence: 99%
“…The hops constituent colupulone forms hydrogen bonds with His407 and bonds to Gln285 through a water molecule (Fig. 3F) (Teotico et al 2008). The PXR-ligand interaction appears to be a dynamic process, leading to structural changes that quite possibly alter the interaction between PXR and its coactivator or corepressor.…”
Section: Structure Of Pregnane X Receptormentioning
confidence: 99%